2010
DOI: 10.1093/ageing/afq052
|View full text |Cite
|
Sign up to set email alerts
|

Hospital use, institutionalisation and mortality associated with delirium

Abstract: Delirium is associated with high rates of institutionalisation and an increased risk of death up to 5 years after index event. Prior to delirium, individuals seem to compensate for their vulnerability. The impact of delirium itself, directly or indirectly, may convert vulnerability into adverse outcome.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
69
0
1

Year Published

2013
2013
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 95 publications
(79 citation statements)
references
References 25 publications
9
69
0
1
Order By: Relevance
“…Delirium is also associated with multiple adverse outcomes including patient falls [5], longer length of stay [6], higher readmission rates [7,8], increased costs of care [9], nursing home placement [10], long-term cognitive impairment [11] and mortality [12].…”
Section: Introductionmentioning
confidence: 99%
“…Delirium is also associated with multiple adverse outcomes including patient falls [5], longer length of stay [6], higher readmission rates [7,8], increased costs of care [9], nursing home placement [10], long-term cognitive impairment [11] and mortality [12].…”
Section: Introductionmentioning
confidence: 99%
“…Studies reporting associated mortality all showed a detrimental effect of delirium even up to 5 years from the index event but by a varying magnitude. 13,19,25,37,41 The need for long-term care following delirium remains a consistent finding in the delirium literature. 2,21,22,26,28,29,33,36,38 Delirium outcomes are studied in the context of confounders such as severity of illness, disability and dementia and would appear to remain an independent predictor of adverse event.…”
Section: Changing Criteria For Delirium Diagnosismentioning
confidence: 89%
“…At tissue and organ system level, frailty has effects on the nervous and endocrine system, manifesting as delirium (21) and dementia (22), chronic inflammation (23,24), sarcopaenia (25), anaemia (26) and coagulopathy, steroid hormone dysregulation (27,28), low vitamin D levels, malnutrition (29,30) and insulin resistance (15,31). This can manifest at host organism level as immobility, instability, incontinence and intellectual impairment, often termed the 'giants of geriatrics' (32).…”
Section: Pathophysiological Mechanisms Of Frailtymentioning
confidence: 99%